2013
DOI: 10.14227/dt200113p13
|View full text |Cite
|
Sign up to set email alerts
|

PhEq_bootstrap: Open-Source Software for the Simulation of f2 Distribution in Cases of Large Variability in Dissolution Profiles

Abstract: PhEq_bootstrap is a free software tool that uses the similarity factor (f 2 ) to assess dissolution profile similarity in cases of large data variability. Its theoretical background is founded on bootstrapping, a statistical technique used to simulate the distribution of f 2 values based on the available sample. It allows both justification of profile similarity and prospective simulations for the establishment of the formulation development endpoint. The software is FOSS (free open-source software) and is ava… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 1 publication
0
22
0
Order By: Relevance
“…Bootstrap of f 2 generates a new population of dissolution profiles through random samples with replacement from 12 units of the test and reference batches, respectively [28, 29]. It is possible to assess the similarity of dissolution profiles with large variability if the data populations are identically distributed.…”
Section: Resultsmentioning
confidence: 99%
“…Bootstrap of f 2 generates a new population of dissolution profiles through random samples with replacement from 12 units of the test and reference batches, respectively [28, 29]. It is possible to assess the similarity of dissolution profiles with large variability if the data populations are identically distributed.…”
Section: Resultsmentioning
confidence: 99%
“…It was found that both mini-tablets containing either 37.5 % w/w or 62.5% w/w co-adsorbate formulations showed nearly identical release profiles due to the similarity of excipients used in the formulations. The F2 similarity factor value for comparison between the two mini-tablet formulations was >50 and the F2 bootstrap values was confirmed as 72.13 indicating a high degree of similarity between the dissolution profiles [24,25]. Both formulations achieved approximately 100±2.74% drug release after 15 mins which were slightly better than the release from 1:5:5 co-adsorbate mentioned before.…”
Section: Dissolution Of Glc From the Prepared Mini-tabletsmentioning
confidence: 87%
“…Calculations of f2 values were based on comparisons between the dissolution profiles for pure GLC, adsorbates, co-adsorbates and mini-tablet formulations. The degree of similarity between dissolution profiles was also confirmed by calculating the f2 values based on the bootstrap statistical approach using the PhEq_bootstrap v 1.2 software (number of bootstraps = 5000 and Confidence Interval = 90%) [25].…”
Section: In Vitro Dissolution Studiesmentioning
confidence: 97%
See 1 more Smart Citation
“…9,13) All data points until average dissolutions of both reference and generic products that reached 85% were used according to FDA recommendations. The datasets of dissolution profiles were created by random sampling of individual dissolution rates at each time point in the original data.…”
Section: Methodsmentioning
confidence: 99%